Lightweight Cryptography for IoT in Wireless Sensor Networks: Evaluating Speck, Simon, and Ascon Using NS-3 - Widodo, Bayu; Fazrie, Mohammad; Parulian, Dudi (SAINTIS Publishing, 2025)
Communication security in Wireless Sensor Networks (WSNs) is a significant challenge in the implementation of the Internet of Things (IoT), particularly in smart city applications which have limitations in energy, memory, and computation. Conventional cryptographic algorithms are generally not suitable for IoT devices due to their complexity and high resource requirements, necessitating lightweight cryptography (LWC) algorithms that can balance security and efficiency. This research evaluates three lightweight encryption algorithms - Speck, Simon, and Ascon - using NS-3 simulations in a multi-hop network scenario with 30 nodes. The parameters analyzed include energy consumption, encryption/decryption time, and communication overhead. The simulation results show a significant trade-off: Speck and Simon excel in energy efficiency and low latency, but their security level is moderate; while Ascon provides stronger security according to NIST LWC standards, but with the consequence of higher energy consumption. The main contribution of this research is the provision of a reproducible NS-3 simulation-based framework that can link security and energy efficiency aspects, while also filling the literature gap, which is still limited to hardware testing. This finding is expected to serve as a practical reference for IoT system designers in determining the appropriate encryption algorithm for smart city application needs, and to open up opportunities for further research on real IoT devices.